Determination of economic injury levels of Helicoverpa armigera (Hubner) in chickpea - Zahid, MA; Islam, MM; Reza, MH; Prodhan, MHZ; Begum, M Rumana (Bangladesh Journal of Agricultural Research, 2009)
Chickpea pod borer Helicoverpa armigera (Hubner) is considered to be one of the major pests of chickpea. The damage potential and economic threshold level for Helicoverpa armigera larvae on chickpea crop were worked out. On an average, single larva per m row reduced the yield to the extent of 155 kg/ha and 157 kg/ha in 2004-05 and 2005-06 cropping season, respectively. The ratio of the value of yield saved to the cost of insecticide application at one larva per m row was 1.06 and 1.12 in 2004-05 and 2005-06, respectively. EILs for Helicoverpa armigera were determined as 12 and 0.95 per m row and ETLs was at 09 and 0 73 larvae per m row in 2004-05 and 2005 - 06, respectively. Key Words: Economic injury, chickpea, pod borer doi: 10.3329/bjar.v33i4.2288 Bangladesh J. Agril. Res. 33(4) : 555-563, December 2008